Developing an English for pharmacy syllabus for Indonesian pharmacy assistants with a focus on speaking skills and specific vocabulary - Fionalita, Melva; da Silva, Anna Marietta (EduLite: Journal of English Education, Literature and Culture, 2026)
English has played a significant role for pharmacy assistants working in retail or hospital pharmacies. However, an English for Pharmacy syllabus that involved both pharmacy assistants and experienced pharmacists has been hardly found. Hence, to fill in the gap and to accommodate the needs for a smooth communication in English at the above workplaces, an English for Pharmacy syllabus should be developed. The aim of the present study is to identify the needs of the Pharmacy students and design a syllabus to respond to the needs. The study adopted a mixed-method approach and focused on the Present Situation Analysis and Target Situation Analysis. As many as 35 pharmacy students who have also been pharmacy assistants, and 6 senior pharmacists were involved in this study. Data was collected through a survey and an interview. Based on the identified needs, a syllabus was designed. Findings indicate that speaking skills were the utmost needed skills, followed by the listening and reading skills. The participants suggested that speaking skills were needed to enable them provide information about medicine to the foreign patients or customers, specifically information on the name, use, dosage, prices, indications, contraindications, side effects, and storage. In addition, the participants pointed out the need to understand symptoms of the diseases that are informed by the patients and to understand the content of drug leaflet or pamphlet. Furthermore, the participants needed to understand technical vocabulary to enable them to notify the medicine information. Grounded on the needs analysis, an eclectic syllabus drawn from the content-based, situational, skill-based, task-based, and notional/functional syllabuses, was designed. The syllabus prioritized speaking skills but necessitates reading and listening skills as a requisite to facilitate the acquisition of the former. The content, including the lexical items, centered on the medicines that were most frequently inquired by the patients.